Balancing climate rights and a just transition in oil-reliant Northern Norway: Entry points and road blocks through SDG localization and municipal planning - Wedwaldt, Allison Ann (2022)
With the Norwegian Supreme Court’s 2020 People v. Arctic Oil decision, the prospects for halting oil and gas production and ensuring climate rights in Norway diminished significantly. This underscores the need to identify other avenues and levels for structural change in Norway, and this project investigates the potential of the local level for doing so. This project uses a case study of Harstad, a municipality that aims to be both “The Environmental City” and “The Oil Capitol of the North,” to shed light on the entry points and road blocks for balancing climate rights, especially the rights of future generations, and a just transition, especially the socioeconomic rights of workers and communities that rely on the oil and gas industry, at the local level. The theoretical framework is a human rights-based approach to sustainable development, which is applied to the processes and outcomes of SDG localization and municipal planning. The methods include (1) document analyses of municipal plans, minutes of municipal council meetings, and the municipality’s consultations with the oil and gas industry, (2) semi-structured interviews with municipal council members, and (3) a closed-question survey delivered to municipal council members and deputy members. The findings reveal a rhetorical, overarching commitment to the SDGs and climate action but a lack of integration of social and environmental interests into economic decision-making regarding the oil and gas industry and a lack of willingness to take transformative mitigation measures regarding this industry that would ensure climate rights and a just transition but may impede economic growth. The findings also confirm the near-total absence of any discourse about substantive climate rights or a just transition at the local level as well as local authorities’ belief in the insignificance of procedural rights in issues related to climate change and the oil and gas industry. This has implications for the transformative capacity of the human-rights based approach at the ...